Investigating trade theory in the case of the Zambian soya value chain - Mwansa, Ruth Miselo (My University, 2016)
This research paper analyses the Zambian soya bean value chain and serves to explore and investigate to what extent trade theory can be used to explain this value chain. Soya bean production in Zambia has grown vastly within the last four years, owing to this growth, Zambia has instantly become a net exporter of soya bean cake. Most of the soya bean cake produced is consumed within the country. The animal feed industry utilises a large percentage of the soya cake in order to produce animal feed for the poultry sector predominantly. The growth in the soya industry has created various linkages for example the poultry industry which is a growing industry owing to amongst other factors, the growth in the Zambian middle class. This research aims to explore the constraints, challenges and drivers of this value chain. Trade theory is used in order to explain the value chain and capture the limitations of theory in relation to the Zambian soya bean value chain. The research paper uses both a qualitative and quantitative methodology. Interviews were used to source information and quantitative data was collected from various platforms
Thesis (M.Com. (Development Theory and Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences.
Keywords: Soybean industry--Zambia